A disease-specific enteral nutrition formula improves nutritional status and functional performance in patients with head and neck and esophageal cancer undergoing chemoradiotherapy: Results of a randomized, controlled, multicenter trial - Fietkau, Rainer; Lewitzki, Victor; Kuhnt, Thomas; Hoelscher, Tobias; Hess, Clemens-F.; Berger, Bernhard; Wiegel, Thomas; Roedel, Claus; Niewald, Marcus; Hermann, Robert M.; Lubgan, Dorota (Cancer, 2013)
Background: In patients with head and neck and esophageal tumors, nutritional status may deteriorate during concurrent chemoradiotherapy (CRT). The aim of this study was to investigate the influence of enteral nutrition enriched with eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) on body composition and nutritional and functional status. Methods: In a controlled, randomized, prospective, double-blind, multicenter study, 111 patients with head and neck and esophageal cancer undergoing concurrent CRT received either an enteral standard nutrition (control group) or disease-specific enteral nutrition Supportan®-containing EPA+DHA (experimental group) via percutaneous endoscopic gastrostomy. The primary endpoint was the change of body cell mass (BCM) following CRT at weeks 7 and 14 compared with the baseline value. Secondary endpoints were additional parameters of body composition, anthropometric parameters, and nutritional and functional status. Results: The primary endpoint of the study, improvement in BCM, reached borderline statistical significance. Following CRT, patients with experimental nutrition lost only 0.82 ± 0.64 kg of BCM compared with 2.82 ± 0.77 kg in the control group (P =.055). The objectively measured nutritional parameters, such as body weight and fat-free mass, showed a tendency toward improvement, but the differences were not significant. The subjective parameters, in particular the Kondrup score (P =.0165) and the subjective global assessment score (P =.0065) after follow-up improved significantly in the experimental group, compared with the control group. Both enteral regimens were safe and well tolerated. CONCLUSION Enteral nutrition with EPA and DHA may be advantageous in patients with head and neck or esophageal cancer by improving parameters of nutritional and functional status during CRT. © 2013 American Cancer Society.
Created from Fastlane, Scopus look-up
Keywords: concurrent chemoradiotherapy; docosahexaenoic acid; eicosapentaenoic acid; esophageal cancer; head and neck cancer; nutritional status; nutritional therapy; supportive care